Transcriptional and Post-transcriptional Control of the Nitrate Respiration in Bacteria - Durand, Sylvain; Guillier, Maude (Frontiers in Molecular Biosciences, 2021)
In oxygen (O2) limiting environments, numerous aerobic bacteria have the ability to shift from aerobic to anaerobic respiration to release energy. This process requires alternative electron acceptor to replace O2 such as nitrate (NO3-), which has the next best reduction potential after O2. Depending on the organism, nitrate respiration involves different enzymes to convert NO3- to ammonium (NH4+) or dinitrogen (N2). The expression of these enzymes is tightly controlled by transcription factors. More recently, bacterial small regulatory RNAs (sRNAs), which are important regulators of the rapid adaptation of microorganisms to extremely diverse environments, have also been shown to control the expression of genes encoding enzymes or transcription factors related to nitrate respiration. In turn, these transcription factors control the synthesis of multiple sRNAs. These results suggest that sRNAs play a central role in the control of these metabolic pathways. Here we review the complex interplay between the transcriptional and the post-transcriptional regulators to efficiently control the respiration on nitrate.